Rituximab in juvenile myasthenia gravis-an international cohort study and literature review. (September 2022) - Ramdas, Sithara; Della Marina, Adela; Ryan, Monique M.; McWilliam, Kenneth; Klein, Andrea; Jacquier, David; Alabaf, Setareh; Childs, Anne-Marie; Parasuraman, Deepak; Beeson, David; Palace, Jacqueline; Jungbluth, Heinz
Abstract: Juvenile myasthenia gravis (JMG) is a rare, antibody-mediated disorder of the neuromuscular junction. Treatment strategies in JMG are largely informed by adult MG treatments as the pathophysiology is similar. Rituximab is increasingly considered as a treatment option in refractory JMG but has not yet been systematically investigated in this patient group We conducted a retrospective study from five international centres with expertise in paediatric myasthenia. 10 JMG patients treated with rituximab were identified. Following rituximab treatment all patients had a reduction in JMG-related hospital admissions. At 24 month follow up, 6 patients (60%) had achieved complete stable remission or pharmacological remission and 7 patients were able to reduce immunomodulatory treatment(s). The main side-effect was infusion-related reactions (30%) which resolved in all patients with symptomatic treatment. We compared our cohort to previously reported JMG cases treated with rituximab and noted similar response rates but a slightly higher side-effect profile. Rituximab is a safe and effective treatment option in moderate to severe JMG and most patients have an improvement in MG symptoms post treatment. Highlights: Rituximab is an effective treatment option in moderate to severe juvenile myasthenia gravis. Post rituximab treatment there is reduction in hospital admissions related to myasthenia gravis and also need for immunomodulatory treatment. Commonest side effect with rituximab is infusion-related reactions and these respond well to standard symptomatic treatments.